Family firms, expropriation and firm value : Evidence from Malaysia / Liew Chee Yoong - Liew, Chee Yoong (2013)
The primary objective of this study is to examine whether minority shareholder expropriation in Malaysian firms occur through related party transactions (RPTs) which are likely to result in expropriation and the domestic banking channel as well as whether it is influence by independent directors’ tenure. An analysis is made on whether this expropriation is stronger in family firms compared to non-family firms. Furthermore, an assessment is also made whether there is a positive moderating effect of controlling shareholders’ ownership on the relationship between related party transactions (RPTs) which are likely to result in expropriation, independent directors’ tenure and the number of domestic banks that the firm engages with, and firm value in Malaysian firms. Further analysis is also made on whether this positive moderating effect (if any) is stronger in family firms compared to non-family firms. This research utilises panel data pooled Ordinary Least Square (OLS) regression model and the Fixed Effect Least Square Dummy Variable (LSDV) model for data analysis. In this research, minority shareholder expropriation is found in both family and non-family firms. However, minority shareholder expropriation through RPTs is found to be stronger in family firms compared to non-family firms. In addition, expropriation due to long tenure of independent directors occur only in family firms in exclusive industries and this expropriation cannot be proven whether it is stronger in family firms or non-family firms. In family firms, corporate reputational effects after the Transmile scandal also help reduce expropriation through the positive moderating effects of controlling shareholders’ ownership. This moderating effects is stronger in family firms compared to non-family firms. Basically, this study shows us that there is a need for the relevant authorities in this country i.e. the Securities Commission (SC) to seriously incorporate minority shareholder protection in future issuance of Codes of Corporate Governance.